The Influence of Price, Promotion and Positive Emotions on Online Impulse Buying with Hedonic Shopping Motivation as an Intervening Variable (Study: Women Fashion Product in Indonesia) - Brabo, Nora Andira; Sari, Nurma Elita; Iswati, Heni; Meidiyustiani, Rinny (Budapest International Research and Critics University, 2021)
Internet users in Indonesia have been growing rapidly and have strong impacts on several aspects of life including the use of online shopping. In Indonesia, more than half of population are exposed to digital world and thus, the growth for online shopping in also increased and projected to reach 43.9 million of online shoppers in 2022. This online shopping can also trigger the consumptive behavior that satisfy the desires of instant gratification that promote consumer’s impulse buying behavior. The purpose of this study is to investigate several factors that lead to impulse buying of online shoppers in Indonesia. We investigate the role of Price, Promotion and Positive Emotions that customer experience toward online impulse buying with Hedonic Shopping Motivation as an intervening variable. Total numbers of 200 female respondents are selected for online survey in capital city of Jakarta and surrounded area. Data were analyzed using Structural Equation Model (SEM). The results shows that Price and Positive Emotions do not affect Hedonic Shopping Motivation, while Promotion has significant effect on Hedonic Shopping Motivation. Price and Positive Emotions have influence on Impulse Buying, while Hedonic Shopping Motivation do not have significant impact on Impulse Buying and fail to act as an intervening variable using SEM. Furthermore, Price, Promotions, Positive Emotions and Hedonic Shopping Motivation as independent variables simultaneously affect Impulse Buying. Implications and limitations are further discussed.